Eenheid in die NG Kerkfamilie: Waar staan die NG Kerk? - Strauss, PJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Unity in the family of Dutch Reformed Churches: Where does the Dutch Reformed Church stand? The story of the process of unity in the family of Dutch Reformed Churches is vulnerable to the ebb and flow of points or situations of consensus and difference. Alack of trust and understanding often brings this process to standstill. The two main issues to solve are the roll and status of the Confession of Belhar in the new church and the structural model which should be used. The DRC are of the opinion that the acceptance of the former can not be used as a condition for unity, although it may be included in the confessional basis of the new church: but as not compulsory for any member of the church. Against this the General Synod of URCSA of 2008 again decided to make the acceptance of Belhar as a confession a condition for the process. They were only willing to proceed with unity talks if it was facilitated by members of the World Alliance of Reformed Churches. It seems as if there are less problems on the proposed structure as put forward by the joint conference of the family at Achterberg in 2007. The proposal is to start with a joint general synod which replaces the existing general synods. The DRC seem prepared to go this way, although the smaller members of the family seem to object. In the mean time the DRC remain committed to the process and are willing to talk to solve any difference or problem.